2008
DOI: 10.4085/1062-6050-43.1.14
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Tool Approach for Face Mask Removal During On-field Conditions

Abstract: Combining the cordless screwdriver and cutting tool provided a fast and reliable means of on-field FM removal in this Division II setting. Despite the excellent overall result, 1 FM was not removed in a timely manner. Therefore, we recommend that athletic trainers practice helmet removal to be prepared should FM removal fail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 5 publications
2
35
0
Order By: Relevance
“…The use of a CSD requires regular charging to ensure proper function. In addition, foreign substances lodged in the screw head, stripped screw heads, 16 and T-nut spinning have been reported in several studies, 15,19 especially on used helmets, 16,21,22 as reasons for failure of screw removal. In our study, 1 removal trial failed because a foreign object was lodged in 1 screw head.…”
Section: Facemask Removal Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of a CSD requires regular charging to ensure proper function. In addition, foreign substances lodged in the screw head, stripped screw heads, 16 and T-nut spinning have been reported in several studies, 15,19 especially on used helmets, 16,21,22 as reasons for failure of screw removal. In our study, 1 removal trial failed because a foreign object was lodged in 1 screw head.…”
Section: Facemask Removal Methodsmentioning
confidence: 99%
“…The participants knelt and positioned themselves with the helmet between their knees to stabilize the model's head and minimize motion of the helmet and cervical spine during the FMR trial. As other investigators have, 10,14,16,17 we selected this position to simulate the worstcase scenario of a single rescuer simultaneously stabilizing the head and removing the facemask.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, many investigators have examined questions related to equipment removal and cervical spine motion, [1][2][3] airway access techniques, 4,5 and techniques and efficiency of face-mask removal. [6][7][8][9][10][11][12][13] Evidence has suggested that airway access can be obtained in the football-helmeted athletes without the removal of the face mask, ultimately reducing motion of the cervical spine often associated with face-mask removal. 4,5,14 However, the National Athletic Trainers' Association 15 and the InterAssociation Task Force for the Appropriate Care of the Spine-Injured Athlete 16 advocate full removal of the football face mask under all circumstances.…”
mentioning
confidence: 99%